USE OF WET CONCRETE SPRAYING IN BUILDING TECHNOLOGY OF REIN-FORCED-CONCRETE FIBER SLABS ACCORDING TO «MONOFANT» SYSTEM - Bugayevskiy, S.; Бугаевский, С. А; Бугаєвський, С. О. (Харьковский национальный автомобильно-дорожный университет, 2016)
Technology of cementation of reinforced-concrete slabs with non-extractable-liners for the «Monofant» system, using wet concrete spraying is implemented. A compression test for obtained columns made of fiber concrete is carried out.
ПРИМЕНЕНИЕ МОКРОГО ТОРКРЕТИРОВАНИЯ ДЛЯ ВОЗВЕДЕНИЯ ИЗ ФИБРОБЕТОНА ЖЕЛЕЗОБЕТОННЫХ КОЛОНН ПО СИСТЕМЕ «МОНОФАНТ»
ЗАСТОСУВАННЯ МОКРОГО ТОРКРЕТУВАННЯ ДЛЯ ЗВЕДЕННЯ З ФІБРО-БЕТОНУ ЗАЛІЗОБЕТОННИХ КОЛОН ЗА СИСТЕМОЮ «МОНОФАНТ»
Keywords: system «Monofant» system; column; non-extractable-liners; fiber concrete; fiber; wet concrete spraying; система «Монофант»; колонна; неизвлекаемый вкладыш-пустото¬образователь; фибробетон; фибра; мокрое торкретирование; система «Монофант»; колона; вкладиш-пустотоутворювач; який не виймається; фібробетон; фібра; мокре торкретування; 693.5